Global Employment and Social Trends. Issue 1 (7th October 2016) - ,
Abstract : The global economy is showing new signs of weakness… The world economy is estimated to have expanded by 3.1 per cent in 2015, over half a percentage point less than had been projected a year earlier. If current policy responses are maintained, the outlook is for continued economic weakening, posing significant challenges to enterprises and workers. Indeed, over the next two years, the world economy is projected to grow by only around 3 per cent, significantly less than before the advent of the global crisis. The continuing slowdown in economic growth is being driven by weakness in emerging and developing countries. China is facing a pronounced slowdown. This, combined with other factors, has contributed to a steep decline in commodity prices, particularly those related to energy. This situation has, in turn, affected large emerging economy commodity exporters, such as Brazil and the Russian Federation, which have entered a period of recession. The benefits accruing to net commodity importers have been insufficient to offset the decline affecting exporters. Another sign of economic weakness is the fact that global trade, which had typically expanded twice as fast as the global economy, is now growing in line with or at a lower rate than global growth.